Managing social media INFORMATION during the Covid-19 pandemic: The TMIM perspective - Tengku Mohd Azzman, Tengku Siti Aisha; A. Manaf, Aini Maznina (2020)
COVID-19 is a novel pandemic that is spreading worldwide. Due to uncertainty surrounding how to manage outbreak and lack of a cure, government and local health agencies have to create awareness among the general public in terms of the severity of the disease, ways to combat infection and standard operating procedures (SOP) regarding the disease. In Malaysia currently, COVID-19 is experiencing its third wave of outbreak in Malaysia. Therefore, this research aims to examine information seeking management regarding COVID-19 on social media among Malaysians based on the theory of motivated information (TMIM) perspective. Findings indicate that as posited by TMIM, emotions such as anxiety partially mediated the information between information discrepancy and social information seeking regarding COVID-19. The implication of this finding on the TMIM perspective, as well as designing health campaigns among the Malaysian public on health issues, will be discussed.